Dissecting the Association of Apolipoprotein E Gene Polymorphisms With Type 2 Diabetes Mellitus and Coronary Artery Disease - Wu, Lei; Zhang, Yan; Zhao, Hong; Rong, Guodong; Huang, Peijun; Wang, Fang; Xu, Ting (Frontiers in Endocrinology, 2022)
Background: Apolipoprotein E (APOE) gene mediates lipoprotein clearance and is one of the most studied candidate genes for Type 2 diabetes mellitus (T2DM) and coronary artery disease (CAD). This study was performed to determine the association between APOE polymorphisms and T2DM with and without CAD, as well as its effect on plasma lipid levels in a Chinese population. Methods: A total of 1414 subjects involving 869 patients and 545 health individuals were recruited. These patients were categorized into three distinct groups, 264 in T2DM group, 401 in CAD group, and 204 in T2DM+CAD group. Logistic regression analysis was used to obtain odds ratio (OR) and 95% confidence interval (CI) in predicting the risk probability of APOE. Besides, a meta-analysis was preformed to integrate an evaluation index to evaluate their associations. Results: Genotype frequency ratio of genotype ε3/4 and allele ε4 among the CAD patients with or without T2DM was obviously increased. Compared with ε3/3 genotype, the ε3/4 genotype had a significant increased risk of CAD (adjusted OR = 1.90, 95% CI = 1.30-2.77) and T2DM+CAD (adjusted OR = 1.95, 95% CI = 1.24-3.08). In the meta-analysis, four studies were included, and provided a strong evidence for the APOE ε4 mutation elevating the risk of CAD in patients with T2DM (ε3/ε4+ε4/ε4 vs. ε3/ε3, OR = 1.51, 95% CI = 1.13-2.02). In T2DM group, the plasma levels of LDL-C showed significant difference among the three APOE isoforms. The HDL-C levels of CAD patients with ε4-bearing genotypes were lower than those with ε3/3 genotype. Conclusions: Our results indicate that APOE gene polymorphisms are related to CAD with or without T2DM, and have influence on lipid profiles in both T2DM and CAD patients.